Nonfat milk attenuates acute hyperglycemia in individuals with android obesity: A randomized control trial. Issue 8 (12th September 2018) - Leary, Miriam P.; Roy, Stephen J.; Lim, Jisok; Park, Wonil; Ferrari, Rodrigo; Eaves, Jared; Machin, Daniel R.; Tanaka, Hirofumi
Abstract: Background: Elevated android body fat increases the risk of developing cardiometabolic diseases. Postprandial hyperglycemia contributes to the proatherogenic metabolic state evident in android adiposity. Due to the insulinotropic effect of milk‐derived proteins, postprandial hyperglycemia has been shown to be reduced with the addition of dairy products. The purpose of this study was to determine whether one serving of nonfat milk added to an oral glucose tolerance test (OGTT) could attenuate postprandial hyperglycemia in individuals with elevated android adiposity and whether these improvements would be associated with metabolic and/or peripheral hemodynamic effects. Methods: In this placebo‐controlled, randomized, crossover experimental study, 29 overweight/obese adults (26 ± 1 year) consumed an OGTT beverage (75 g glucose) combined with either nonfat milk (227 g) or a placebo control (12 g lactose + 8 g protein + 207 g water) that was matched for both carbohydrate and protein quantities. Results: In the whole sample, blood glucose and insulin concentrations increased over time in both trials with no significant differences between trials. Relative increases in peak blood glucose response were significantly related to android body fat ( p < 0.05). The subjects in the highest tertiles of android body fat displayed attenuated hyperglycemic responses as well as improvements in flow‐mediated dilation (FMD) after milk intake. Conclusions: A single serving of nonfat milk may attenuate acute hyperglycemia in individuals with elevated android body fat offering a simple and convenient option for managing elevations in blood glucose. Abstract : Due to the insulinotropic effect of milk‐derived proteins, postprandial hyperglycemia has been shown to be reduced with the addition of dairy products. The purpose of this study was to determine whether one serving of nonfat milk added to an oral glucose tolerance test (OGTT) could attenuate postprandial hyperglycemia in individuals with elevated android adiposity and whether these improvements would be associated with metabolic and/or peripheral hemodynamic effects. The subjects in the highest tertiles of android body fat displayed attenuated hyperglycemic responses as well as improvements in FMD after milk intake.